Computing as writing - Punday, Daniel (University of Minnesota Press, 2015)
"This book examines the common metaphor that equates computing and writing, tracing it from the naming of devices ('notebook' computers) through the design of user interfaces (the 'desktop') to how we describe the work of programmers ('writing' code). Computing as Writing ponders the implications and contradictions of the metaphor, which isn't simply a set of techniques or a collection of technologies but also an idea that resonates throughout contemporary culture. He addresses a wide array of subjects, including film representations of computing (Desk Set, The Social Network), Neal Stephenson's famous open source manifesto, J.K. Rowling's legal battle with a fan site, the sorting of digital libraries, subscription services like Netflix, and the Apple versus Google debate over openness in computing. Punday shows how contemporary authors are caught between traditional notions of writerly authority and computing's emphasis on doing things with writing. What does it mean to be a writer today? Is writing code for an app equivalent to writing a novel? Should we change how we teach writing? Punday's answers to these questions and others are original and refreshing, and push the study of digital media in productive new directions."--Back cover